Evaluation of Fluorescent Capillary Electrophoresis for Rapid Identification of Candida Fungal Infections - Obručová, Hana; Tihelková, Radka; Kotásková, Iva; Růžička, Filip; Holá, Veronika; Němcová, Eva; Freiberger, Tomáš (Journal of clinical microbiology, 2016)
Early diagnosis of fungal infection is critical for initiating antifungal therapy and reducing the high mortality rate in immunocompromised patients. In this study, we focused on rapid and sensitive identification of clinically important Candida species, utilizing the variability in the length of the ITS2 rRNA gene and fluorescent capillary electrophoresis (f-ITS2-PCR-CE). The method was developed and optimized on 29 various Candida reference strains from which 26 Candida species were clearly identified, while Candida guilliermondii, C. fermentati, and C. carpophila, which are closely related, could not be distinguished. The method was subsequently validated on 143 blinded monofungal clinical isolates (comprising 26 species) and was able to identify 88% of species unambiguously. This indicated a higher resolution power than the classical phenotypic approach which correctly identified 73%. Finally, the culture-independent potential of this technique was addressed by the analysis of 55 retrospective DNA samples extracted directly from clinical material. The method showed 100% sensitivity and specificity compared to those of the combined results of cultivation and panfungal PCR followed by sequencing used as a gold standard. In conclusion, this newly developed f-ITS2-PCR-CE analytical approach was shown to be a fast, sensitive, and highly reproducible tool for both culture-dependent and culture-independent identification of clinically important Candida strains, including species of the "psilosis" complex.
Keywords: polymerázová řetězová reakce; DNA, Fungal; elektroforéza kapilární; Candida; mezerníky ribozomální DNA; kandidóza; DNA fungální; Time Factors; lidé; Candidiasis; Humans; mikrobiologické techniky; Sensitivity and Specificity; senzitivita a specificita; časové faktory; DNA, Ribosomal Spacer; Polymerase Chain Reaction; Electrophoresis, Capillary; Microbiological Techniques